A Sea of Fiction: The Libraries of Trans-Pacific Steamships at the Turn of the Twentieth Century. (23rd February 2019) - Liebich, Susann
Abstract: Reading has always been part of travel, whether by rail, road or ship. This article focusses on the interrelationship between libraries and sea travel, the dominant form of global transport for much of the nineteenth and twentieth centuries. While travel diaries and fictional accounts of sea travel are replete with references to shipboard reading, they reveal little about what texts passengers consumed or how they accessed reading material. Drawing on a number of extant catalogues and records of ships' libraries on passenger steamers operating in the Pacific as well as on travellers' accounts, this article considers the provisions and usage of ships' libraries in the late nineteenth and early twentieth centuries. The catalogues reveal that these libraries on the move provided predominantly topical, bestselling and entertaining fiction, catering to (perceived) demands for distraction and short-term reading pleasure.